Effect of Organic and Inorganic Nutrient Sources on Yield and Quality of Fodder Cowpea [Vigna unguiculata (L.) Walp.] - Dutta, Susanta; Singh, Magan; Meena, Rajesh Kumar; Basak, Nirmalendu; Mondal, Goutam; Hindoriya, Phool Singh (Indian Journal of Animal Nutrition, 2019)
A field experiment was conducted to study the effect of organic and inorganic nutrient sources on yield and quality of fodder cowpea [Vigna unguiculata (L.) Walp.] during kharif, 2017 at Research Farm of Agronomy Section, ICAR- National Dairy Research Institute, Karnal. Significantly higher green fodder yield (334.5 q ha-1), Dry matter content (17.80%) and dry matter yield (59.5 q ha-1) were obtained with the application of RDF (N,P,K) along with biofertilizers (Rhizobium, Phosphorus Solubilizer Bacteria, Potassium Solubilizer Bacteria and Zinc Solubilizer Bacteria). Application of 2/3rd RDF along with biofertilizers (Rhizobium, PSB, KSB and ZnSB) significantly enhanced the quality parameters of fodder cowpea like crude protein (18.30 %), ether extract (3.48%) and total ash content (8.82%) while Insoluble crude protein (NDICP & ADICP), Organic matter and fiber fractions (NDF, ADF, ADL) were significantly lowered. Whereas lignin content had no significant differences among the treatments.Â